2017
DOI: 10.31233/osf.io/j4rk7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental drivers of crocodyliform extinction across the Jurassic/Cretaceous transition

Abstract: Crocodyliforms have a much richer evolutionary history than represented by their extant descendants, including several independent marine and terrestrial radiations during the Mesozoic. However, heterogeneous sampling of their fossil record has obscured their macroevolutionary dynamics, and obfuscated attempts to reconcile external drivers of these patterns. Here, we present a comprehensive analysis of crocodyliform biodiversity through the Jurassic/Cretaceous (J/K) transition using subsampling and phylogeneti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…; Tennant et al . , ), and the same was hypothesized for plesiosaurs (Benson & Druckenmiller ). However, the hypothesized turnover among plesiosaurs could in part be explained by poor sampling: few plesiosaur specimens are known from this time interval.…”
supporting
confidence: 55%
“…; Tennant et al . , ), and the same was hypothesized for plesiosaurs (Benson & Druckenmiller ). However, the hypothesized turnover among plesiosaurs could in part be explained by poor sampling: few plesiosaur specimens are known from this time interval.…”
supporting
confidence: 55%
“…Pachycheilosuchus was originally described as a possible atoposaurid (Rogers 2003), but Turner (2015) recovered it at the base of Eusuchia. Other studies have recovered this species in radically different positions, such as: in a more basal position within Neosuchia, closer to the split with Tethysuchia (Adams 2014); as a derived neosuchian but basal to Eusuchia (Narváez et al 2015); as a basal neosuchian, even more basal than the Tethysuchia-Eusuchia split (Tennant et al 2016b); or in a clade with an assortment of hylaeochampsids and susisuchids (Schwarz et al 2017). The phylogeny of Turner (2015) is consistent with Buscalioni et al (2011) in the monophyly of Hylaeochampsidae, despite the fact that the latter study found Pietraroiasuchus as the sister group of Pachycheilosuchus (although they did not sample Acynodon).…”
Section: Implications Of Nms G2016211 As a Potential Hylaeochampsidmentioning
confidence: 99%
“…However, the various phylogenetic analyses appear to converge on a divergence between the large-bodied and primarily aquatic neosuchian clades (Pholidosauridae þ Dyrosauridae) and the relatively smaller-bodied, terrestrial or semi-aquatic clades (although the position of Goniopholididae is variable; Adams 2014; Turner 2015; Young et al 2016b;Schwarz et al 2017). Yet little is known about neosuchians before the Late Jurassic due to a patchy non-marine fossil record (Mannion et al 2015;Tennant et al 2016b). The earliest definitive record of pholidosaurid material comes from the Late Jurassic of Uruguay and France (Fortier et al 2011).…”
Section: Implications Of Nms G2016211 As a Potential Hylaeochampsidmentioning
confidence: 99%
See 2 more Smart Citations